Anatomical description of the sinus in the alpaca (Vicugna pacos) - Zárate L., Rosse (2015)
The objective of the present study was to describe the macroscopic anatomy of the sinus in the alpaca. Ten skulls of adult alpacas were prepared by the maceration technique, and the description through longitudinal cuts was done using terminology recommended by the Nomina Anatomica Veterinaria. In addition, X-rays with contrast medium were taken to four adult alpacas to determine the relationships of sinus with other anatomical structures. Results showed that the frontal and maxillary sinus were well developed and communicated through the frontomaxillary hole; the frontal sinus is divided into a medial and lateral portion as in small ruminants; the maxillary sinus is undivided and has a communication with the nasal cavity through the nasomaxillary opening as in the equine. The sphenoid and ethmoid sinuses were not evident.